Electromagnetic induction with time-varying magductance under constant magnetic field - Wei Qin; Ming Cheng; Xinkai Zhu; Zheng Wang; Wei Hua (AIP Advances, 2024)
Electrical energy is becoming more popular due to the fact that it is economic, practical, clean, and easy to control and convert energy compared to other forms of energy. Currently, however, most of the electrical energy is converted from or to mechanical energy based on the well-known Faraday’s law of electromagnetic induction, which states that a current will be induced in a closed conductive coil exposed to a changing magnetic field. For that purpose, either the magnetic field itself must be changing or the magnetic field must be moving relative to the closed conductive coil. While investigating the physical significance of magductance (or magnetic-inductance), we unearthed a new electromagnetic induction mechanism that the electrical current is induced in a closed conductive coil with the invariant magnetic field by changing the magnetic parameter of magductance of the closed coil. Time-varying magductance is achieved by changing the conductivity of the coil. To demonstrate the feasibility of the electromagnetic induction, both theoretical validation and experimental verification are undertaken. We built a closed superconducting coil and successfully measured the induced electrical currents in the cooling process of the closed superconducting coil under an invariant magnetic field, thus verifying the new law of electromagnetic induction.